2020
DOI: 10.1038/s41598-020-59644-6
|View full text |Cite
|
Sign up to set email alerts
|

Matching STR and SNP genotyping to discriminate between wild boar, domestic pigs and their recent hybrids for forensic purposes

Abstract: the genetic discrimination between phylogenetically close taxa can be challenging if their gene pools are not differentiated and there are many shared polymorphisms. The gene flow between wild boar (Sus scrofa) and domestic pig (S. s. domesticus) has never been interrupted from domestication onwards, due to non-stop natural and human-mediated crossbreeding. To date there are no individual genetic markers that are able to distinguish between the two forms, nor even to identify effectively their hybrids. We deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 43 publications
0
30
0
1
Order By: Relevance
“…Different clinical signs, immunological responses, and pathological outcomes are also known for highly pathogenic porcine reproductive and respiratory syndrome virus infection in wild boar and domestic pigs [ 32 ]. So far, genetic discrimination between domestic pigs and wild boar has been challenging since there have been only few genetic markers identified to distinguish between domestic pigs and wild boar [ 33 ], and even immunogenetic investigation of domestic pigs and wild boar could not identify any statistically significant differences in allele frequency and heterozygosity across SNPs [ 34 ]. However, very recently SLA-1 diversity was investigated in different domestic pig breeds showing significant distribution of SLA-1 alleles among pig breeds which could explain differences in the immune response [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different clinical signs, immunological responses, and pathological outcomes are also known for highly pathogenic porcine reproductive and respiratory syndrome virus infection in wild boar and domestic pigs [ 32 ]. So far, genetic discrimination between domestic pigs and wild boar has been challenging since there have been only few genetic markers identified to distinguish between domestic pigs and wild boar [ 33 ], and even immunogenetic investigation of domestic pigs and wild boar could not identify any statistically significant differences in allele frequency and heterozygosity across SNPs [ 34 ]. However, very recently SLA-1 diversity was investigated in different domestic pig breeds showing significant distribution of SLA-1 alleles among pig breeds which could explain differences in the immune response [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NR6A1 gene, encoding an orphan nuclear receptor, is located in a 300-kb region that is fixed in a variety of European commercial breeds (Landrace, LW, Yorkshire, Duroc, and Berkshire) (1). This gene has been focused on as a means of controlling economically important traits in the swine market or as a tool to discriminate between wild boar and domestic pigs (19,27,28). We found that the Microminipig was homozygous for the NR6A1 C/C genotype, with a vertebrae number of lower than the 19 vertebrae uniformly found in wild boar (3,23).…”
Section: Discussionmentioning
confidence: 99%
“…A combination of the mitochondrial Cytochrome-b gene ( Cyt-b ) with 12 microsatellite loci was beneficial and allowed a successful investigation of poaching of the Cypriot mouflon ( Ovis orientalis ophion ), wherein three shot mouflon were discovered, and bloodstained items were seized from a suspect’s vehicle [ 5 ]. Use of a porcine-specific STR system and real time PCR-based assays of single nucleotide polymorphisms in the NR6A1 and MC1R genes was proposed for discrimination of wild boars from domestic pigs, and validated for forensic purposes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%